A Fournier Gangrene Severity Index and Diabetes Mellitus: A Significance Correlation among Fournier Gangrene Patients in Single Center Hospital - Faeni, Hanum; Wibisono, Wibisono; Putra, Galih Santosa; Putra, Muhammad David Perdana (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Fournier gangrene (FG) is an urological emergency in the form of progressive necrotizing fascitis caused by polymicrobial infection which affects the perineum and external genitalia. FG that is not diagnosed and treated properly will result in severe morbidity and even mortality for the patient. The assessment of FG becomes clearer with the creation of a scoring system that predicts patient prognostic and therapeutic outcomes, known as the Fournier ganggreen severity index (FGSI). This FGSI includes clinical and laboratory examinations, namely, temperature, pulse, respiratory rate, levels of sodium, potassium, leukocytes, hematocrit, and blood serum bicarbonate. AIM: We aimed to present descriptive retrospective study, which examined the relationship between age and DM with FGSI in FG patients at the Regional General Hospital. METHODS: Data were taken from January 2017 to December 2020 at the Urology Department, dr. Moewardi Hospital Surakarta. There were 32 cases of FG patients, consisting of 20 patients with diabetes mellitus (DM) and 12 non-DM patients. RESULTS: This study found that FG patients with an FGSI score <9 were 24 patients (75%), FG patients with an FGSI score of >9 were 8 patients (25%). Judging by the distribution of the FGSI score according to the age of the FG patient using the chi-square technique, the value p = 0.045. The p-value <0.05 means that at the 5% significance level the difference in the proportion of FGSI scores between age categories of FG patients is significant. The distribution of the FGSI score according to the DM comorbid showed that there were nine patients with an FGSI score of >9 (45.5%) with comorbid DM and no patients without the DM comorbid. Result of statistical test using the Chi-square technique was p = 0.036. The p-value < 0.05 means that at the 5% significance level the difference in the proportion of FGSI scores between patients with and without comorbid DM is significant. CONCLUSION: Judging by the distribution of the FGSI score, it can be concluded that there is significant relationship between the age of the FG patient and the FGSI score and there is a significant relationship between the DM comorbid and the FGSI score in FG patients at dr. Moewardi Hospital Surakarta in the period January 2017 to December 2020.